Uncovering the Mechanism(s): Financial Constraints and Wages - Hamzeh Arabzadeh; Almut Balleer; Britta Gehrke (Institute of Labor Economics (IZA), 2020)
How do wages respond to financial recessions? Based on a dynamic macroeconomic model with frictions in the labor and the financial market, we address two prominent mechanism through which firms' financial constraints amplify unemployment and explore their effect on wages. First, the financial labor wedge reduces wages. Second, financial constraints may interact with aggregate labor market conditions in various ways putting upward or downward pressure on wages. We test partial-equilibrium implications of these theoretical mechanisms based on a large data set for Germany for 2006 to 2014 that combines administrative data on workers and wages with detailed information on the balance sheets of firms. Both mechanisms play a role empirically. Using our estimates as central calibration targets in our model, we document that financial recessions are associated with a substantial decline in both unemployment and wages. Financial constraints therefore weaken the direct link between wage rigidity and unemployment volatility.
Keywords: E32; E44; J63; J64; 330; financial frictions; wages; search and matching; unemployment; business cycles